Massive retroperitoneal lipoblastoma in a three-year-old child: A case report - Grace Boyd; Dylan Kendrick; Roy Kimble (Elsevier, 2023)
Introduction: Lipoblastoma is a rare soft tissue tumour that occurs predominantly in infants and children. They are slow growing and occur intra-abdominally only ∼10% of the time. Due to their benign nature and slow progression, intra-abdominal lipoblastomas have been described to produce few symptoms. Case Presentation: A three-year-old male was referred with a large asymptomatic abdominal mass, incidentally noted by their GP. His abdomen was obviously distended but soft. Laboratory investigations were within reference ranges for his age. CT imaging found a large abdominal mass thought to arise from the retroperitoneum. The mass was excised via exploratory laparotomy, weighing 1.736kg. Histopathological assessment supported the diagnosis of lipoblastoma. Conclusion: Surgical removal allows for a definitive diagnosis of lipoblastoma to be made. It is important to differentiate lipoblastomas from simple lipomas or myxoid liposarcomas due to the varying clinical management and surveillance requirements. Considering this child and earlier cases described in the limited literature, we propose that knowledge of, and clinical assessment for lipoblastoma is important to allow for timely investigation and appropriate management.